The relationship between job satisfaction and affective commitment among support staff in hotel industry in Temerloh, Pahang / Nor Baizura Mohd Zubaidi, Rasidah Razak and Suriana Md Suwandi - Mohd Zubaidi, Nor Baizura; Razak, Rasidah; Md Suwandi, Suriana (2010)
The purpose of this study was to investigate the relationship between job satisfaction and affective commitment among support staff in hotel industry in Temerloh, Pahang. The scope of the study were the support staff who were working in six hotels in Temerloh Pahang, which include Green Park Hotel, Seri Malaysia Hotel, Jelai Hotel, Semantan Hotel, New Swiss Hotel and Kam San Hotel. In this study, the researchers used disproportionate stratified random sampling technique. The instruments were adopted from Krejcie and Morgan (1970). This correlation study used survey questionnaires which have been distributed to 100 respondents and the return rate was 95%. Data analyze were done by using PSAW 18.0. The major findings in this study indicated that there was small significant relationship between job satisfaction and affective commitment (r=0.40, p= <0.01). This study showed that the majority of the respondents agreed that elements of work itself and pay contributed to their affective commitment. This study also found out that age level of support staffs contributed to a high affective commitment. From the finding, there were some recommendations given to the organization. First, top management should improve the knowledge about job satisfaction. It is also highlighted that top management should increase the job satisfaction among its support staff because it could contribute to their highest affective commitment. Another suggestion is to improve the quality of training among support staff. It is suggested that the employees should be given training to increase self-awareness. The top management of hotel industry in Temerloh, Pahang may use these findings in increasing the affective commitment of support staff in their organization. The researchers also suggested that future study should look into more sample size and several other elements in order to ensure generalizability.